Preparation of zein nanoparticles by using solution-enhanced dispersion with supercritical CO2 and elucidation with computational fluid dynamics - Li S (Dove Medical Press, 2017)
Sining Li, Yaping Zhao School of Chemistry and Chemical Engineering, Shanghai Jiao Tong University, Shanghai, China Abstract: Nanoparticles have attracted more and more attention in the medicinal field. Zein is a biomacromolecule and can be used as a carrier for delivering active ingredients to prepare controlled release drugs. In this article, we presented the preparation of zein nanoparticles by solution-enhanced dispersion by supercritical CO2 (SEDS) approach. Scanning electron microscopy and transmission electron microscopy were applied to characterize the size and morphology of the obtained particles. The nozzle structure and the CO2 flow rate greatly affected the morphology and the size of the particles. The size of zein was able to be reduced to 50–350 nm according to the different conditions. The morphologies of the resultant zein were either sphere or the filament network consisted of nanoparticles. The influence of the nozzle structure and the CO2 flow rate on the velocity field was elucidated by using computational fluid dynamics. The nozzle structure and the CO2 flow rate greatly affected the distribution of the velocity field. However, a similar velocity field could also be obtained when the nozzle structure or the CO2 flow rate, or both were different. Therefore, the influence of the nozzle structure and the CO2 flow rate on the size and morphology of the particles, can boil down to the velocity field. The results demonstrated that the velocity field can be a potential criterion for producing nanoparticles with controllable morphology and size, which is useful to scale-up the SEDS process. Keywords: nozzle structure, supercritical antisolvent, zein nanoparticles, computational fluid dynamics